Family language policy and bilingual parenting in monolingual Beijing: latent profiles and associated predictors. Issue 9 (21st October 2022) - Li, Hui; Wu, Dandan; Degotardi, Sheila; Chik, Alice
ABSTRACT: This study explored the family language policy, parental beliefs, and bilingual parenting in Beijing, a typical monolingual society. Stratified random sampling was conducted to recruit 192 parents of Chinese preschoolers (ages 2.5, 3.5, 4.5, and 5.5 years). They were surveyed with the Home Language Environment and Practices (HLEP) developed for this study. The statistical results indicated that: (1) the majority of Beijing families (90.1%) did not have bilingual home environment or related family language policy, only 8.9% did so; (2) three latent classes of bilingual parenting emerged: ' No Explicit Policy ' (lower parental education level, no extra-curriculum activities, no bilingual environment, no Chinese-English bilingual, and few books at home; 64.6%); ' Monolingual Parenting ' (relatively higher parental education level, more extra-curriculum activities, the highest number of Chinese and English books at home, the longest time for Chinese storytelling, and an emphasis on Chinese literacy and language learning; 26.6%); and ' Bilingual Parenting ' (the highest parental education level, Chinese-English bilingual parents, bilingual home environment, and relatively more Chinese and English books at home); and (3) parental education level, bilingual father, bilingual mother, and number of English books at home predicted the profile of bilingual parenting, whereas parental beliefs about early bilingualism did not.